DEVELOPMENT OF EMPLOYEE PERFORMANCE MODEL BASED ON TRANSACTIONAL LEADERSHIP, COMPETENCY, AND JOB SATISFACTION - Darmanto, Susetyo; Supriyadi, Yan (Universitas Brawijaya, Indonesia, 2022)
This study aims to analyze the effect of transactional leadership style and employee competence on the performance of Miclyn Express Offshore Pte.Ltd employees either directly or indirectly through job satisfaction. The populations in this study are all employees who work at Miclyn Express Offshore Pte. Ltd. The sample used is employees with a total of 73 respondents, and the sampling technique used is stratified random sampling. The data sources used are primary data, with a questionnaire data collection method. The analytical technique used is path analysis and the Sobel test. The results obtained that transactional leadership style and competence had a positive and significant effect on job satisfaction. Transactional leadership style and competence had a positive and significant effect on employee performance, and job satisfaction had a positive and significant effect on employee performance. Based on the Sobel test, it was found that job satisfaction can mediate the effect of transactional leadership style and competence on employee performance. Management must continue to pay attention to the abilities possessed by each employee, especially in terms of increasing self-confidence, theoretical ability, practical ability, expertise, and consistency of each employee, so that it will have an impact on improving their performance.